Design of a Medical Guide and Healthy Lifestyle Application for Pregnant Women Based on Flutter Web Mobile - Br. Panggabean, Chaterine Laura; Anggara, Afwan (Universitas Trilogi, 2025)
Pregnancy is a period women that requires careful health monitoring and access to accurate medical information, yet pregnant women still face limitations in accessing digital platforms that provide structured health guidance. This study focuses on developing a web-mobile application using the Flutter framework to deliver medical guidelines and healthy lifestyle recommendations for pregnant women at Puskesmas Mlati 1 Yogyakarta. The development process applies the Waterfall model, which includes requirement analysis, system design, implementation, testing, and maintenance. The main features of the application include medical guidelines, a medical terminology dictionary, healthy food recommendations, examination schedule checking, and daily healthy lifestyle tips. The user interface is designed to be responsive and easy to use, enabling users to access the provided information conveniently. The testing results show that the application runs well across various devices and is capable of supplying the information needed by pregnant women throughout their pregnancy. This application is expected to serve as a practical and educational information tool that supports the improvement of maternal health literacy through digital technology.